نسیم حجازی کا ناول معظم علی ـــــــــــــــ ایک تجزیاتی مطالعہ (Al-Aasar, 2025)
Naseem Hijazi's Novel “Moazzam Ali” is a story that marks a historical moment where no action or thought is acceptable beyond human freedan in Moazzam Ali; Naseem Hijazi Completely Captivates the reader. Through this novel, Hijazi Presents the intellectual midset prevalent in India, Which through the character of Moazzam Ali, nol only teaches us tolerance and palience but also narrates the lake of bravery intelligence, and the Struggle of thought and action - a struggle that remains.